(untitled) (Research, Society and Development, 2020)
Objective: to assess the nurse’s performance in the prevention and treatment of users with diabetic foot in the Family Health Strategy. Methodology: qualitative, descriptive and exploratory study. The participants were 10 nurses who worked in the Family Health Strategies, in a municipality in Northwestern Rio Grande do Sul. Data collection occurred during the August and September 2019, through semi-structured interview, using the Thematic Content Analysis. Results: the the participants develop actions related to prevention, control and treatment provided to patients with diabetic foot. The success of the service is based on health education actions and nursing consultation. Conclusions: nurses perform direct care with the lesion, including dressings, choice of coverages and, when necessary, the referral of patients to other professionals of the multidisciplinary team and to other services.